The emergence of prolonged deadly humid heatwaves - Xiang‐Sheng Wang; Lei He; Xiao‐Hu Ma; Qiang Bie; Lin Luo; You‐Cai Xiong; Jian‐Sheng Ye (International Journal of Climatology, 2022)
Deadly humid heat conditions exceeding human thermoregulatory capacity have been reported; however, whether and where the deadly humid heat events occur consecutively across the land surface are largely unknown. We calculate the maximum consecutive days of deadly humid heat, defined as daily maximum wet‐bulb temperature (TWmax) ≥35°C, for observations of 9,278 meteorological stations and for simulations of 14 global climate models. We further define short and long deadly humid heatwaves as a period of 3–4 and ≥5 consecutive days with daily TWmax ≥35°C, respectively. Our analyses show that six stations in some subtropical regions have experienced deadly humid heat with daily TWmax ≥35°C, but only occurs in individual days. Deadly humid heatwaves increase exponentially as the global mean temperature rising. When limiting global warming within 1.5°C, long deadly humid heatwaves will not occur across the land surface, and short deadly humid heatwaves will only emerge in some drylands but not in humid areas. Under 2°C warming, 0.09% of the global land, 0.42% of the human population, and 0.56% of the global centres of crop diversity are projected to be exposed to long deadly humid heatwaves. Meanwhile, 18% of the deadly humid heatwaves lasting ≥3 consecutive days will occur in humid areas; the fractions are projected to rapidly increase in humid areas as temperature rising further. At the end of the century, the percentage of land areas and human population exposed to deadly humid heatwaves lasting ≥3 consecutive days are expected to be 76‐times higher than that under 1.5°C warming level. Our finding suggests that keeping global warming within 1.5°C will significantly constrain the emergence of prolonged deadly humid heatwaves and thus reduce the risk of the human population especially outdoor agricultural workers.